2018
DOI: 10.19173/irrodl.v19i2.3469
|View full text |Cite
|
Sign up to set email alerts
|

Reflection on MOOC Design in Palestine

Abstract: This paper will share Discover Palestine, an interdisciplinary Massive Online Open Course (MOOC) and the first MOOC to be created in Palestine, by the E-Learning Centre, Faculty from the Department of Geography, and Department of Tourism and Archaeology from An-Najah National University in Palestine. The paper traces the process of development of the Discover Palestine MOOC from its early inception as a cross institutional online course, to its current delivery and engagement with a global and diverse group of… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
6
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
6
2
1

Relationship

2
7

Authors

Journals

citations
Cited by 10 publications
(6 citation statements)
references
References 10 publications
0
6
0
Order By: Relevance
“…Each learning context has its own characteristics that may demand a specific course design to meet educational needs. Therefore, research suggests to develop e‐learning initiatives through interdisciplinary design teams with diverse professional backgrounds, like content experts, technology experts, educationalists, etcetera (Affouneh et al, 2018; Salvador & Rodríguez‐Hoyos, 2016).…”
Section: Discussionmentioning
confidence: 99%
“…Each learning context has its own characteristics that may demand a specific course design to meet educational needs. Therefore, research suggests to develop e‐learning initiatives through interdisciplinary design teams with diverse professional backgrounds, like content experts, technology experts, educationalists, etcetera (Affouneh et al, 2018; Salvador & Rodríguez‐Hoyos, 2016).…”
Section: Discussionmentioning
confidence: 99%
“…This situation requires an in-depth analysis of key aspects such as teachers' professional competences [35] in higher education. Those competences are not limited to using certain technological tools or performing mechanical tasks [36] but also include reaching out for pedagogical and learning management requirements, which are essential for the transformation of an online, open college experience [37].…”
Section: Discussionmentioning
confidence: 99%
“…Wang et al (2016) characterized MOOC as it meets the needs of different styles of learning, open, interactive, and also has rich resources, despite of its large size. Affouneh et al (2018) concluded that MOOC offers opportunities for sharing, understanding creative practices and cultural issues.…”
Section: What Is Mooc?mentioning
confidence: 99%
“…In the Palestinian higher educational institutions, many attempts have been documented to develop and deliver MOOCs courses individually or with cooperation with international universities (Affouneh et al, 2018). An interdisciplinary Massive Online Open Course (MOOC) was the first MOOC to be created in Palestine, as a collaboration project between the E-Learning Centre, Faculty from the Department of Geography, and Department of Tourism and Archaeology from An-Najah National University in Palestine with an International University in the USA (Affouneh et al, 2018). The ANNU developed and delivered a new MOOC course after the success of the first one.…”
Section: Introductionmentioning
confidence: 99%